1992
DOI: 10.1037/0735-7028.23.5.362
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in the practice of clinical psychology.

Abstract: The study tested a theory that confidence in practice is associated with 6 variables. A random sample of 425 (0.8%) of the 53,000 clinical psychologists in private practice in the US in 1988 received a questionnaire by mail: 369 of the questionnaires reached eligible, practicing clinical psychologists; 174 (47%) were returned and usable. Of the 174, there were 111 men and 56 women, and 7 did not report their gender. Sixty-six were in solo practice; 51 in group practice; 26 in clinics, hospitals, or mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Satisfaction with this initial training was more strongly related to therapeutic confidence than subsequent work experience, engagement in psychotherapy‐related CPD, or having additional formal psychotherapy training. This corresponds with past reports that work experience was less important for confidence than length of training (Melchert et al, ) and less important than belief in clinical psychologists' capacity for therapeutic work (Glidewell & Livert, ). This suggests that early training experience may be critical for establishing clinical psychologists' therapeutic confidence, with an impact that can persist throughout their careers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction with this initial training was more strongly related to therapeutic confidence than subsequent work experience, engagement in psychotherapy‐related CPD, or having additional formal psychotherapy training. This corresponds with past reports that work experience was less important for confidence than length of training (Melchert et al, ) and less important than belief in clinical psychologists' capacity for therapeutic work (Glidewell & Livert, ). This suggests that early training experience may be critical for establishing clinical psychologists' therapeutic confidence, with an impact that can persist throughout their careers.…”
Section: Discussionmentioning
confidence: 99%
“…Longer time in training has been found to contribute to greater counselling self-efficacy, to a greater degree than later experience (Melchert, Hays, Wiljanen, & Kolocek, 1996), but further studies reported mixed findings regarding length of training and selfefficacy (see Tang et al, 2004). With clinical psychologists, greater therapeutic confidence was related to more therapeutic experience but a stronger predictor of confidence was the belief that clinical psychologists were equipped to practice psychotherapy from their clinical training (Glidewell & Livert, 1992).…”
Section: Exploring Factors Contributing To Therapeutic Confidencementioning
confidence: 99%
“…Perceived control Das and Teng (1998); Hanton and Connaughton (2002); Cofta (2007) Self-efficacy Tafarodi, Mehranvar, Panton, and Milne (2002); Bekkers (2006); Glidewell and Livert (1992) Bekkers (2006) a Trust can be classified as an idiosyncratic factor when it refers to the tendency of individuals to extend trust in others or as a situation factor when it refers to trust extended to others in given circumstances.…”
Section: Conceptual Foundations and Definitions Of Confidencementioning
confidence: 99%
“…Following this line of thought, several authors define “confidence” as a certainty that a given professional task or approach will bring about an expected, favorable outcome,20 as well as a belief in one’s judgment and abilities 21,22. In the present study, “clinical confidence” is understood in terms of encouragement and exploration of new professional frontiers.…”
Section: Discussionmentioning
confidence: 96%